Two year follow-up of long-stay chronically mentally ill inpatients transferred to the community : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology, Massey University - Huzziff, Robyn (Massey University, 1995)
The present study was undertaken to evaluate the affect of transferring long-stay chronically mentally ill clients from Lake Alice Hospital to community placements. Thirty chronically mentally ill clients were followed over two years in the community. Follow-up assessments were completed at 12, 18, and 24 months to assess clients' community adjustment. Community adjustment was conceptualised to include measures of general adaptive functioning, maladaptive behaviour, inpatient readmission, client satisfaction, subjective well-being, and levels of distress. The results showed that clients' general adaptive functioning and deviant behaviour remained stable from the hospital baseline assessment into the community follow-up phases. With respect to client characteristics, clients who exhibited more maladaptive behaviour were found to be significantly more likely to be readmitted to a psychiatric unit or hospital, and older clients were more likely to be socially isolated and exhibit poorer levels of adaptive functioning. Many clients remained socially isolated from family and friends, suggesting that if community support were withdrawn neglect may occur. Clients were significantly more satisfied with community than hospital services at 12 months follow-up and clients were found to be globally satisfied with community services. Nevertheless, up to 10% of client's showed poor community adjustment, with frequent readmissions to a psychiatric hospital, poor adaptive functioning, and high levels of maladaptive behaviour and distress. The implications of the findings for chronically mentally ill clients and service providers are discussed, with several recommendations for future research.
Keywords: Mental illness care; Chronically ill; Community mental health services; Deinstitutionalization; New Zealand